1983
DOI: 10.2172/59299
|View full text |Cite
|
Sign up to set email alerts
|

Overview of low temperature sensitization

Abstract: This report was prepared as an account of work sponsored by an agency of the United Slates Government. Neither the United States Govetnraw.t nor any agency thereof, nor any of their employees, makes any warranty, express or implied, or assumes any legal liability or responsi bility for the accuracy, completeness, or usefulness of any informalion, apparatus, product, or process disclosed, or reptesents that ils use viould not infringe privately owned rights. Refer ence herein to any specific commercial product,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Chromium carbide precipitation in stainless steels occurs in the temperature range of 500 to 850°C (during pouring of vitrified glass into a canister the outside cansiter walls can reach 550°C [54]), and the rate of precipitation is controlled by chromium diffusion [5]. It is generally accepted that the mechanism for sensitization is the creation of a narrow chromium-depleted zone that forms contiguous to the carbides.…”
Section: Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium carbide precipitation in stainless steels occurs in the temperature range of 500 to 850°C (during pouring of vitrified glass into a canister the outside cansiter walls can reach 550°C [54]), and the rate of precipitation is controlled by chromium diffusion [5]. It is generally accepted that the mechanism for sensitization is the creation of a narrow chromium-depleted zone that forms contiguous to the carbides.…”
Section: Sensitizationmentioning
confidence: 99%
“…Sensitized structures may be problematic in oxidizing environments, particularly in cases where gamma radiation from waste forms generates radiolysis reactions in the water, which will likely make the water more oxidizing [54].…”
Section: Sensitizationmentioning
confidence: 99%
“…The cumulative effects of time at temperature during welding and subsequent very long times at moderately elevated temperatures in the repository are additive in forming sensitized microstructures. This possibility of low temperature sensitization (LTS) was analyzed by Fox and McCright <1983), who concluded that heavily cold-worked AISI 304L (0.028 wt.% C) could develop a sensitized structure after as little as 10 yr at an isothermal surface temperature of 280°C. This analysis was based on extrapolating the results from the work of Brian* (1982) in support of investigations on sensitized 300-series stainless steels under boiling water reactor (BWR) environmental conditions.…”
Section: Low Temperature Sensitizationmentioning
confidence: 99%
“…The analysis of Fox and McCright (1983) considered some of the mitigating effects that the environment might have, even on a sensitized stainless steel. First, the dominant environment for tens to hundreds of years after emplacement would be unsaturated stc.im at temperatures above 96°C.…”
Section: 4 Environmental Effects On 1gscc Susceptibilitymentioning
confidence: 99%
“…The line for 304L sensitization was obtained by extrapolation of data obtained at higher temperatures (450-750°C). This particular material had a carbon content (0.028X) near the top of the permitted range and was heavily cold-worked [8]. Both of these conditions enhance susceptibility to sensitization.…”
Section: Container Corrosion Rates and Mechanismsmentioning
confidence: 99%